Carbon and tree diversity in agricultural systems in Nicaragua: do trees really make a difference? - Siles, P.; Valbuena, Diego; Castro, A.; Tellez, O.; Bonilla, G.; Hoek, Rein van der (2015)
The Soils Research Area presents a new seminar series to commemorate the International Year of Soils (2015). This seminar series which in LAC will run under the theme: Managing Soils for Smarter Societies, will include monthly presentations and blogs that will focus on soils and the role they play in our society. Presented by Dr. Pablo Siles who is based at the CIAT office in Nicaragua.